The dual glucose‐dependent insulinotropic polypeptide and glucagon‐like peptide‐1 receptor agonist tirzepatide improves cardiovascular risk biomarkers in patients with type 2 diabetes: A post hoc analysis. Issue 1 (11th October 2021) - Wilson, Jonathan M.; Lin, Yanzhu; Luo, M. Jane; Considine, Gary; Cox, Amy L.; Bowsman, Lenden M.; Robins, Deborah A.; Haupt, Axel; Duffin, Kevin L.; Ruotolo, Giacomo
Abstract: In a phase 2 trial of once‐weekly tirzepatide (1, 5, 10, or 15 mg), dulaglutide (1.5 mg), or placebo, the dual glucose‐dependent insulinotropic polypeptide and glucagon‐like peptide‐1 receptor agonist tirzepatide dose‐dependently reduced HbA1c and body weight in patients with type 2 diabetes. In this post hoc analysis, inflammation, endothelial dysfunction, and cellular stress biomarkers were measured at baseline, 4, 12, and 26 weeks to evaluate the additional effects of tirzepatide on cardiovascular risk factors. At 26 weeks, tirzepatide 10 and 15 mg decreased YKL‐40 (also known as chitinase‐3 like‐protein‐1), intercellular adhesion molecule 1 (ICAM‐1), leptin, and growth differentiation factor 15 levels versus baseline, and YKL‐40 and leptin levels versus placebo and dulaglutide. Tirzepatide 15 mg also decreased ICAM‐1 levels versus placebo and dulaglutide, and high‐sensitivity C‐reactive protein (hsCRP) levels versus baseline and placebo, but not dulaglutide. GlycA, interleukin 6, vascular cell adhesion molecule 1, and N‐terminal‐pro hormone B‐type natriuretic peptide levels were not significantly changed in any group. YKL‐40, hsCRP, and ICAM‐1 levels rapidly decreased within 4 weeks of treatment with tirzepatide 10 and 15 mg, whereas the decrease in leptin levels was more gradual and did not plateau by 26 weeks. In this hypothesis‐generating exploratory analysis, tirzepatide decreased several biomarkers that have been associated with cardiovascular risk.